2013 IEEE 26th International Conference on Micro Electro Mechanical Systems (MEMS) 2013
DOI: 10.1109/memsys.2013.6474188
|View full text |Cite
|
Sign up to set email alerts
|

Large power amplification of a piezoelectric energy harvester excited by random vibrations

Abstract: This paper reports the method and results of amplifying the power output of a piezoelectric energy harvester excited by random vibrations. The amplification is achieved by applying a dual-mass-spring system. A maximum power amplification of 80 times has been experimentally demonstrated. The generated power output from a piezoelectric energy harvester, when excited by asmeasured random vibrations, amounts to 28.9 µW. This is sufficient to operate a battery-free Tire Pressure Monitoring System (TPMS) for wireles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…There are several methods that can be utilised, may it be by altering the shape of the piezoelectric specimen, changing its geometry and incorporating multiple layers of piezoelectric material. These advancements can be observed from the references [4], [5], [6], [7], [8], [9] and [10]. In all cases, we can observe that the structure or configuration of the energy harvester is modified in some way.…”
Section: Modification On Piezoelectric Energy Harvestersmentioning
confidence: 75%
“…There are several methods that can be utilised, may it be by altering the shape of the piezoelectric specimen, changing its geometry and incorporating multiple layers of piezoelectric material. These advancements can be observed from the references [4], [5], [6], [7], [8], [9] and [10]. In all cases, we can observe that the structure or configuration of the energy harvester is modified in some way.…”
Section: Modification On Piezoelectric Energy Harvestersmentioning
confidence: 75%
“…Power generation from repetitive shock excitation has been experimentally demonstrated previously [21][22]. In reality, repetitive shock excitation can be found at the contact patch The authors are with the Holst Centre/Stichting imec Nederland, 5656 AE Eindhoven, The Netherlands (e-mail: ziyang.wang@imec-nl.nl; rene.elfrink@imec-nl.nl; madelon.rovers@imec-nl.nl; svetla.matova@ imec-nl.nl; rob.vanschaijk@imec.be; michael.renaud@imec-nl.nl).…”
Section: Introductionmentioning
confidence: 99%
“…In previous work, Elfrink et al [1] demonstrated a MEMS harvester powered wireless sensor node with the harvester generating 10 W DC power under steady sinusoidal conditions. This work was further progressed by the same group towards the development of a harvester-powered wireless sensor under noisy conditions generating 28.9 W ac power across a matched load for a TPMS application [2]. However, though subsequent work demonstrated MEMS harvesters delivering sufficient DC power (10's W) for automotive applications, concerns around reliability under high shock and vibration have remained [3].…”
Section: Introductionmentioning
confidence: 99%